2014
DOI: 10.1186/0717-6287-47-30
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of different developmental stages of the edible mushroom Termitomyces heimii

Abstract: BackgroundTermitomyces heimii is a basidiomycete fungus that has a symbiotic relationship with termites, and it is an edible mushroom with a unique flavour and texture. T. heimii is also one of the most difficult mushrooms to cultivate throughout the world. Little is known about the growth and development of these mushrooms, and the available information is insufficient or poor. The purpose of this study was to provide a base of knowledge regarding the biological processes involved in the development of T. hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Laccase enzyme which is known to play a key role in biosynthesis of melanin has been also reported from Termitomyces (Bose et al 2007; Gangwar et al 2016). Rahmad et al (2014) identified sulphite reductase enzyme from T. heimii which plays a key role in sulphur assimilation. Our results indicate that Termitomyces species may have efficient sulphur metabolism involving an unidentified pathway linked to O-acetylserine to form cysteine (Leustek et al 2000; Kopriva and Koprivova 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Laccase enzyme which is known to play a key role in biosynthesis of melanin has been also reported from Termitomyces (Bose et al 2007; Gangwar et al 2016). Rahmad et al (2014) identified sulphite reductase enzyme from T. heimii which plays a key role in sulphur assimilation. Our results indicate that Termitomyces species may have efficient sulphur metabolism involving an unidentified pathway linked to O-acetylserine to form cysteine (Leustek et al 2000; Kopriva and Koprivova 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously stated that more enzymes are involved in cell wall synthesis during fruiting body formation than at the mycelium and primordial stages. However, enzymes related to cell wall component degradation were higher expressed at the earlier stages of mushroom growth ( Rahmad et al, 2014 ). Total phosphorus and potassium content in the substrate was lowest at the elongation stage, likely attributable to a high nutrient demand of G. lucidum at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…An induction in stage 1 primordia was observed in both, but, whereas upregulation in A. ampla was > 2009 compared to VM, it was only 149 in S. commune. Aspartic proteases of the A1 family have been reported as highly induced in fruiting bodies in several previous studies (Martin et al, 2008;Sabotic et al, 2009;Rahmad et al, 2014;Song et al, 2018;Krizs an et al, 2019), but no mechanistic hypothesis for their role in fruiting bodies has yet been proposed.…”
Section: Transcriptomics Reveals a High Rate Of Developmental Evolutionmentioning
confidence: 99%